A New Method of Network Index Data Forecast - Zhigang Ni (Dianxin kexue)
As the expansion of communication industry, the network data tends to be diverse, comp1ex and numerous.Therefore, the management and optimization become more and more difficu1t.And the index data forecast requires higher and higher accuracy.How to manage the network data effective1y and comprehensive1y turns to be a capita1 issue.A new method of network index data forecast was studied.